Co-Movement and Integration Among Stock Markets : A Study of 14 Countries - Patel, Ritesh Jayantibhai (Indian Journal of Finance, 2017)
This paper explored the comovement among 14 stock markets, namely BSE, BVSP, FTSE -100, Hang Seng, JKSE, KSE, KSE (Korea), MXX, NASDAQ, NIKKI, RTS, SSE, SSMI, and TSEC. Daily index of all stock markets covering a period from January 1, 1998 to January 31, 2017 were used. The correlation analysis showed that BSE remained somewhat positively correlated with Hang Seng (0.45), FTSE-100 (0.32), MXX (0.27), NASDAQ (0.24), and BVSP (0.23). Results of Granger causality test indicated that the returns of BSE were dependent on BVSP, FTSE - 100, and MXX only. Outcome of Johansen cointegration test indicated that there was a long run relationship among selected stock markets. From this present study, FIIs (foreign institutional investors), individual investors, institutional investors, public investors, and HNIs (high net worth individuals) will be benefited. All theseÂ stakeholders can take their decisions for their investments in the overseas markets by looking at the short-term and long-term integration of BSE with other selected markets.